Nasal Provocation Test with Cat and Dog Extracts: Results according to Molecular Components - Sánchez, Andres; Cardona, Ricardo; Munera, Marlon; Calvo, Victor; Tejada-Giraldo, Manuela; Sánchez, Jorge (Pulmonary Medicine, 2020)
Background. IgE sensitization (atopy) to pets is commonly evaluated using pet dander extracts. However, the diagnosis by components seems to be more adequate to evaluate the clinical relevance (allergy) of sIgE sensitization. Objective. To study the association between IgE sensitization to pet allergen components and clinical symptoms. Methodology. Dander extracts and sIgE levels to pet components (Can f 1, Can f 2, Can f 3, Can f 5, Fel d 1, Fel 2, and Fel 4) were measured in a rhinitis group (n=101) and a control group (n=68). Nasal provocation tests with pet extract were done in patients with atopy to pets. Results. Dog (34.6% vs. 23.5%) and cat dander (26.7% vs. 8.8%, p=0.05) IgE sensitization was frequent among rhinitis and no-rhinitis subjects, and it was similar to dog (29.7% vs. 20.5%) and cat (18.8% vs. 8.8%) components. Polysensitization for dog (3.1, 95% CI: 1.5 to 6.1, p<0.001) or cat (2.5, 95% CI: 0.8 to 8.0, p=0.01) components was the principal risk factor for a positive nasal provocation test. Additionally, positive nasal provocation test with one animal increased the risk of atopy and positive nasal provocation test to others animals. Pet ownership or asthma was not associated with increased risk of atopy or positive nasal provocation test. Conclusions. Sensitization to pet dander extract identifies atopic patients, but its utility to predict clinical relevance is poor. Allergenic components could help to define the clinical relevance of sensitization to furry animals and could reduce the need for provocation test.